The impact of Acehnese respect to customization, corporate reputation and airline service quality to switching barriers and customer loyalty: A study of airline customers in Indonesia - Syafruddin Chan; Zainal Putra; Kurnia Asni (Proceedings of AICS - Social Sciences, 2017)
This study aimed to observe the impact of Acehnese Respect to Customization, Corporate Reputation and Airline Service Quality to Customer Loyalty with Switching Barriers as a mediating variable. The finding of this study would very use full to enrich the references how ethnical culture factor will also have a contribution to developing customer loyalty among airlines customers. Questionnaires distributed in the International Airport of Indonesia with Acehnese Ethnic segment as its primary target respondents.  This survey was using probability sampling techniques to define its sample and respondents. Data were collected and then be analyzed using covariance Based SEM, AMOS. Hypothesis test results proved that there was a positive and significant influence among four variables examined in the study, both directly and indirectly. Although all the independent variables affect Customer Loyalty as dependence variable either directly or indirectly, but a more powerful influence given by variable of Airline Service Quality, compared to four other variables. This is shown by the coefficient numbers on the arrows leading to Customer Loyalty of 0.60 which is the highest coefficient compared to coefficients from other variables. Among the indicators that make up the Airline Service Quality, the indicator "Very friendly cabin crew service and ground staff” has the highest value with a score of 0.843. So this indicator was also played significant role to increase the Customer Loyalty of airline industry in Indonesia.